2022
DOI: 10.3390/jcm11164676
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Soy Isoflavones in the Prevention of Bone Loss in Postmenopausal Women: A Systematic Review with Meta-Analysis of Randomized Controlled Trials

Abstract: The aim of the report was to determine the effects of soy isoflavones on lumbar spine, femoral neck, and total hip bone mineral density (BMD) in menopausal women. MEDLINE (PubMed), EMBASE, and Cochrane Library databases were searched for articles published in English during 1995–2019. Studies were identified and reviewed for inclusion and exclusion eligibility. Weighted mean differences (WMD) were calculated for each study and were pooled by using the random effects model. Eighteen randomized controlled trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
0
8
0
3
Order By: Relevance
“…Subgroup analysis of bone markers showed that isoflavones were more effective in individuals suffering from overweight/obesity [29]. Subsequent meta-analyses provide similar results and conclusions [30,31]. In view of these observations, it can be generally argued that soy isoflavone consumption reduces bone loss associated with menopause, although the effect is modified by different factors, including the dose used and duration of this diet.…”
Section: Impact Of Isoflavonoids On Bone Mineral Densitymentioning
confidence: 79%
See 1 more Smart Citation
“…Subgroup analysis of bone markers showed that isoflavones were more effective in individuals suffering from overweight/obesity [29]. Subsequent meta-analyses provide similar results and conclusions [30,31]. In view of these observations, it can be generally argued that soy isoflavone consumption reduces bone loss associated with menopause, although the effect is modified by different factors, including the dose used and duration of this diet.…”
Section: Impact Of Isoflavonoids On Bone Mineral Densitymentioning
confidence: 79%
“…In the available scientific sources, there are five meta-analyses addressing the effect of isoflavones on BMD [27][28][29][30][31]. The authors of the first meta-analysis assessed urinary deoxypyridinoline (DPyr), which was selected as a marker of bone resorption, and bALP, a marker of bone formation.…”
Section: Impact Of Isoflavonoids On Bone Mineral Densitymentioning
confidence: 99%
“…These improvements include, but are not limited to, hot flashes, mind fog, mood swings, and increased spinal bone density in post-menopausal women [149][150][151][152][153]. While the mechanism by which isoflavone increases bone density is not fully understood, multiple studies have linked increased isoflavone consumption with an increase in bone mineral density [154]. Pre-menopausal women suffering from polycystic ovarian symptom (PCOS) also saw improvements in their symptoms, including better insulin resistance [155].…”
Section: Uses Of Isoflavones In Research and Future Directionsmentioning
confidence: 99%
“…The analysis showed that a daily intake of 106 (range, 40–300) mg of isoflavones for 6–24 months improved bone mineral density (BMD) in different sites, compared with controls. The effects of isoflavones on BMD might be associated with the treatment duration, ethnicity, time after menopause, form of supplements, and dose of isoflavones [ 26 ].…”
Section: Nutraceuticalsmentioning
confidence: 99%